Hepatitis B Virus Immunity Gap: A Six-Year Laboratory Data Review of Hepatitis B Serological Profiles in Gauteng Province, South Africa - Nonhlanhla Mbenenge; Kathleen Subramoney; Clement Gascua Adu-Gyamfi; Florette K. Treurnicht (Advances in Virology)
Background. In 1995, the hepatitis B vaccine in South Africa was incorporated into the childhood expanded programme of immunization. We report on immunity gaps of laboratory-based hepatitis B virus (HBV) among patients in public facilities in Gauteng Province from 1st January 2014 to 31st December 2019. Methodology. We analyzed HBV serological data extracted from the National Health Laboratory Services Central Data Warehouse (NHLS CDW). A descriptive analysis was performed for hepatitis B surface antigen (HBsAg), antibodies to HBV core (anti-HBc) total, anti-HBc IgM, and antibodies to HBV surface antigen (anti-HBs) according to annual distribution, age groups, and sex. Results. The HBsAg positivity rate was 7.0% (75,596/1,095,561; p=0.001): 7.4% (96,532/944,077) in the 25 years and over age group and 4.0% (358/9,268 and 325/10,864) in the under 5 and 13–24 year age groups. The positivity rates of the other HBV serological markers were as follows: anti-HBc total was 37.0% (34,377/93,711; p < 0.001), anti-HBc IgM was 2.4% (5,661/239,237; p=0.05), and anti-HBs was 37.0% (76,302/206,138; p≤0.001). Naturally acquired HBV immunity was detected in 25.7% (11,188/43,536) of patients in the 25 years and over age group, and 9.7% and 8.2% (113/1,158 and 541/6,522) among those under 5 years and 13–24 year age group, respectively (p < 0.001). Vaccine-induced immunity was 56.6% (656/1,158) in children under 5 years and 10.2% (4,425/43,536) among those 25 years and above (p < 0.001). Fifty-six percent (29,404/52,581) of patients were HBV seronegative; predominantly among patients in the 13–24 year age group (60.6%; (3,952/6,522)) and 25 years and over (56.3% (24,524/43,536)) (p=<0.001). Conclusion. The HBV infection seroprevalence remains high in South Africa, with Gauteng province having high intermediate endemicity. However, the HBV immunity gap has shifted from younger children to older children and adults.